Pengaruh Love Of Money Dan Dender Terhadap Pengelolaan Keuanagan Pribadi Pada Generasi Z Di Kota Mojokerto - Dilla Agustin; Nersiwad Nersiwad; Yuliasnita Verlandes (Jurnal Mutiara Ilmu Akuntansi, 2023)
This research is motivated by the existence of financial problems in the younger generation, namely the influence of love of money and gender on personal financial management in generation Z in Mojokerto City. This study uses primary data obtained from distributing questionnaires distributed to respondents. In this study, a sampling technique was used, namely random sampling from a total of 14,857 population so that the number obtained from the calculation of the slovin formula was 99 respondents which were rounded up to 100 respondents. The analytical method to be used in this study uses multiple linear regression analysis using SPSS ver. 22 data needed to score the data, plan the tests that will be used to input data and analyze the answers to each hypothesis or research question. as well as, used to examine the relationship between love of money on financial management and gender on financial management in generation Z in Mojokerto City. The results of this study indicate that love of money partially has a significantly positive effect on personal financial management, gender partially has a significantly positive effect on personal financial management.